Kandungan Antosianin dan Karotenoid serta Komponen Produksi pada Kacang Panjang Berpolong Ungu dan Hijau - Reswari, Helvi Ardana; Syukur, Muhamad; Suwarno, dan Willy Bayuardi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Breeding improved yardlong bean varieties is not only aimed for yield, but also for enhancing nutritional content such as anthocyanin and carotenoids concentrations. The objectives of this research were to elucidate the anthocyanin and carotenoids concentrations as well as yield components in several yard long bean genotypes. This research was conducted at the Leuwikopo Experimental Station and Post Harvest Laboratory of Department of Agronomy and Horticulture IPB from November 2017 to January 2018. The experiment was arranged in a single-factor randomized complete block design with 4 replicates, involving 15 yardlong bean genotypes. The results showed that Fagiola 2 had relatively high anthocyanin and carotenoids contents. Peleton had higher yield than Kinaya 1, Pangeran Anvi, Parade, and Fagiola 2. Anthocyanin content was not correlated with yield components, whereas carotenoids content was positively correlated with the length of pod stalks, length of pods, weight per pod, chlorophyll a, chlorophyll b, and total chlorophyll. Pod weights per plant were positively correlated with the number of pods per plant (r = 0.81, P<0.01), and can be predicted by a linear model involving number of pods per plant and days to harvest (R2 = 0.75, P<0.01).Keywords: biofortification, chlorophyll, correlation, stepwise regression, Vigna unguiculata var. sesquipedalis